Penerapan Teknologi Holografi dalam Pengembangan Aset Pariwisata Edukasi Industri Gerabah Desa Pagelaran - Iriaji, Iriaji; Prasetyo, Abdul Rahman; Ratnawati, Ike; Aruna, Alby; Surya, Eka Putri; Marcelliantika, Adinda; Wijaya, Ginanjar Atma (VISA: Journal of Vision and Ideas, 2024)
This community service program aims to apply holography technology in developing educational tourism assets for the pottery industry in Pagelaran Village. The methodology includes tourism needs analysis, holographic content design, and the evaluation of holography technology implementation. This program is designed to visually and interactively showcase the pottery-making process, providing an immersive educational experience for tourists. The results indicate a significant increase in tourist interest and understanding of the pottery industry. Evaluations through surveys and in-depth interviews confirm that holography technology effectively enhances tourism appeal and educational value. This program makes a significant contribution to modernizing educational tourism assets and ensuring the sustainability of the pottery industry in Pagelaran Village.